Starting the Conversation: Exploring the Meaning, Scope and Contributions of AI and Its Implications for African Psychology - Munnik, James; Nwoye, Augustine (PINS-Psychology in Society, 2025)
This commentary aims to open up a critical debate on the meaning, scope, and contributions of artificial intelligence (AI) with special reference to its implications for African Psychology (AP). The paper sees the potential for collaboration between AI technologies, particularly generative AI and the continued development and evolution of the emerging field of African psychology. This conversation hopes to inspire the endurance of critical discussion on the importance of AI in offering new pathways for enhancing low-cost mental health services, bridging language barriers, fostering cross-cultural understanding and improving research, particularly here in continental Africa. Ethical considerations are also explored vis-à-vis the currently unstoppable influx of AI technologies in the various ramifications of national health systems, and the economy.